Vertical stratification and stability of biogeochemical processes in the deep saline waters of Lake Vanda, Antarctica. (25th September 2019) - Schutte, Charles A.; Samarkin, Vladimir A.; Peters, Brian; Madigan, Michael T.; Bowles, Marshall; Morgan‐Kiss, Rachael; Casciotti, Karen; Joye, Samantha
Abstract: Lake Vanda is a permanently ice‐covered lake in the McMurdo Dry Valleys of Antarctica. Its bottom waters remain stratified year‐round because of a strong salinity‐driven density gradient. We have assessed spatial patterns in and relationships between major biogeochemical processes in the water column of Lake Vanda. Samples were collected in the austral summers of 2008 and 2011 to measure concentrations of metabolites associated with a suite of biogeochemical processes across the deep salinity gradient. The shapes of the resulting geochemical profiles were consistent between 2008 and 2011. Metabolite production and consumption rates were estimated using a reactive transport model based on the assumption that vertical diffusion was the only active physical transport process. We validated this model for nitrification by using stable isotope incubations to show that this process was only active at depths predicted by the model. No nitrification activity was observed at 68 m depth in spite of overlapping oxygen and ammonium gradients. We attribute this lack of activity to the competitive inhibition of ammonia monooxygenase by methane. Net nitrous oxide and nitrate consumption were observed in the oxic water column, providing evidence of aerobic denitrification. The depth of maximum net oxygen production did not coincide with the deep chlorophyll maxima (at 59.3, 63, and 68.2 m) measured in the same profile. Finally, the integrated sulfide oxidation rate was high compared with other oxidation processes, indicating that sulfide was an important electron donor for the water column microbial community.